A historical review of glassy carbon: Synthesis, structure, properties and applications. (October 2021) - Uskoković, Vuk
Abstract: In a letter to her older brother from 1947, soon after she had arrived in Paris, Rosalind E. Franklin said that she was ready to 'go more primitive' if this would preserve her freedom. Influential studies on amorphous carbons released prior to her work notwithstanding, fate would have it that by the end of her postdoctoral studies in Paris in 1950, she would provide a seminal insight into the structure of glassy carbon (GC), possibly the most primitive and anarchic of all high-tech materials. Its synthesis, structure, properties and applications are reviewed here from chronological perspectives, focusing on the conceptual milestones in the evolution of the scientific knowledge on it. Fundamentals of the synthesis of GC are elaborated, including the history of its production in the form of particles. Major advances in understanding the complex structure of GC are discussed by focusing on different characterization techniques utilized in the course of these structural elucidations. The most outstanding physical properties of this material, including the anomalous ones, are also summed, along with the complete chronology of reports on its biological properties. In the final section, the numerous applications of GC are being reviewed, including those in electrochemistry, catalysis and self-assembly, as well as in biosensing and biomaterials. Biomedical applications of GC are shown to have been sporadic since its discovery, but a positive trend is traced, showing an increasing interest in this applicative aspect of GC.